Corneal myofibroblasts and fibrosis - Wilson, Steven E. (Experimental eye research, 2020)
Myofibroblasts are alpha-smooth muscle actin (SMA)+ cells that have a critical role in the corneal stromal response to infections, injuries, and surgeries, and which produce corneal scarring fibrosis when they develop in excess. These contractile and opaque cells—produce large amounts of disordered extracellular matrix (ECM)—and develop from keratocyte-derived corneal fibroblasts or bone marrow-derived fibrocytes, and possibly other cell types, in response to TGFβ1, TGFβ2 and PDGF from the epithelium, tears, endothelium, and other stromal cells. Recent proteomic analyses have revealed that the myofibroblasts that develop from different progenitors aren't interchangeable, but have major differences in protein expression and functions. Absence or defective regeneration of the epithelial basement membrane (EBM) and/or Descemet's basement membrane (DBM) results in development and persistence of myofibroblasts in the corneal stroma. The functions of myofibroblasts in the cornea include production of volume-additive ECM, tissue contraction, production of various growth factors, cytokines and chemokines that regulate stromal cells, including other myofibroblasts, production of collagenases and metalloproteinases involved in tissue remodeling, and the expression of toll-like receptors that likely have critical roles in the clearance of bacteria and viruses causing corneal infections. •Myofibroblasts are the major contributor to corneal fibrosis after injury or infection.•Myofibroblasts are dependent on TGF beta-1 or-2 for development and survival.•Corneal myofibroblasts are derived from keratocyte- and fibrocyte-derived precursors.•Myofibroblasts derived from different precursors have differential gene expression.